Analysis of microbial diversity and community structure of rhizosphere soil of Cistanche salsa from different host plants - Liu, Ailing; Li, Yuxia; Wang, Qiqi; Zhang, Xinrui; Xiong, Jie; Li, Yang; Lei, Yonghui; Sun, Yanfei (Frontiers in Microbiology, 2022)
Host plants influence rhizosphere microorganism composition through root secretions, and rhizosphere associated microorganisms influence Cistanche seeds germination. At present, little is known about effects of different host plants on soil bacteria and fungi in the rhizosphere of Cistanche salsa. High-throughput sequencing was used here to reveal the similarities and differences in the structural composition of the soil microbial community of C. salsa from six host plants (i.e., Halocnemum strobilaceum, Atriplex patens, Kalidium foliatum, Caroxylon passerinum, Anabasis aphylla, Krascheninnikovia ceratoides). We discovered that Krascheninnikovia ceratoides-parasitizing C. salsa (YRCR6) had the highest diversity of rhizosphere bacterial communities, and Anabasis aphylla -parasitizing C. salsa (YRCR5) had the highest diversity of rhizosphere fungal communities. Fungal communities were more influenced by the host plant than bacterial communities. In addition, we discovered certain rhizosphere microorganisms that may be associated with Cistanche seeds germination, including Mortierella, Aspergillus alliaceus and Cladosporium, which are account for a relatively high proportion in Anabasis aphylla -parasitizing C. salsa. Redundancy analysis results also revealed that AP, HCO3−, pH, Ca2+, SO42−, and K+ had a highly significant impact on the bacterial community structure (P<0.01), while pH and SO42− had a significant impact on the fungal community structure (P<0.05). Conclusively, differences were noted in the structure of rhizosphere bacterial and fungal communities of C. salsa parasitizing different plants in the same habit and the difference is related to the host plant. This result can provide a basis for the selection of host plants and the cultivation of C.salsa.